KAJIAN PENGGUNAAN ALGORITMA GUZMÁN DAN SANTAELLA (2009) DALAM PEMETAAN TOTAL SUSPENDED SOLID (TSS) DI PERAIRAN DELTA MAHAKAM - Arifin, Dawamul (GEOID, 2017)
TSS (Total Suspended Solid) is a parameter used to measure the rate of sedimentation. Observation value of TSS can be done using remote sensing methods by utilizing an algorithm to extract TSS value from image satellite. Various kinds of algorithms were developed to obtain the value of TSS which the development of this algorithm is based on the conditions of area. The diversity of existing TSS algorithm makes the need to do a study to find the best algorithms. Mapping the value of TSS in the water region of Delta Mahakam is done using algorithms Guzmán and Santaella (2009). This research was conducted to get information about the best algorithms of Guzmán and Santaella (2009) algorithm for use in the water region of Delta Mahakam and to obtain information about sedimentation rate. The results showed that TSS value from all three algorithms Guzmán and Santaella (2009) have a stronger relation with TSS values from in situ data. This relation showed by correlation value of all three algorithms which reached 75% - 77%. Algorithm 1 capable of providing correlation value 75,25% with rmse 12,2 mg/l. Algorithm 2 providing correlation value 75,26% with rmse 4,7 mg/l whereas the algorithm 3 providing correlation Value 77,35% with rmse 49,64 mg/l. This result showing that algorithm 2 are the best algorithm to get TSS value using Terra MODIS satellite image in the water region of Delta Mahakam. All algorithm produce different TSS value, algorithm 3 produces the biggest TSS value followed by the value of TSS generated from algorithms 1 and then from algorithm 2. Algorithms 1 and 2 show that TSS value in the water region of Delta Mahakam are in low grade (0- 100 mg / l), while the algorithm 3 shows the diversity TSS value. Distribution of TSS using all three Guzmán and Santaella (2009) algorithms has the same pattern in which the value of TSS is greater for location of water region near shoreline than the location of water region far away from the shoreline.